Strategi pemeliharaan sarana dan prasarana sekolah berbasis lingkungan berkelanjutan - Ansori, Ahmad; Mardiah, Mardiah; Syifaul Qalby, Muhammad; Wahyuningsih S, Anita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The maintenance of school facilities and infrastructure plays a vital role in supporting an optimal learning process. This study aims to examine various maintenance strategies for school facilities and infrastructure based on the principles of environmental sustainability. Using a literature study method, the researcher analyzed a range of scholarly sources, educational policies, and best practices from both national and international educational institutions. Data analysis was conducted through content analysis techniques, focusing on thematic reviews of collected textual documents. Data were obtained using documentation techniques by gathering relevant sources from various academic platforms such as Google Scholar, ResearchGate, DOAJ, and university publication portals. The findings indicate that effective maintenance strategies not only emphasize technical and functional aspects but also consider energy efficiency, waste management, the use of environmentally friendly materials, and the active participation of school communities. A sustainable approach to facility maintenance is believed to foster a healthy, safe, and environmentally conscious learning environment. The implications of this study offer strategic recommendations for schools and policymakers in integrating sustainability values into educational facility management